Corporate social responsibility of transnational - de Araujo, Juliana Frauches (2020)
The lack of international corporations legal personality is a central question. There is no supranational law restricting the corporation groups activities. However, many instruments are made to ease the integration of corporation’s social accountability, but these initiatives are not enforceable, and that limits their efficiency. Transnational corporations must promote, respect, uphold and protect human rights in their business, in accordance with the exercise of their authority on the sphere of influence which caused the damage. Nowadays, a responsible corporation is concerned with sustainable development in the management of their activities. However, there is no law to compel the transnational corporations to act responsibly.